Preparation method of regenerated denitration catalyst based on reconstructed bulk phase carrier
By using ultrasonic treatment with ethylenediaminetetraacetic acid-hydrofluoric acid, hydrothermal reconstruction of the TiO2 support, Ce and Zr doping, and gradient calcination to form a five-element interface, the activity and stability problems of vanadium-titanium-based SCR denitration catalysts were solved, achieving high-efficiency denitration performance and long lifespan.
Patent Information
- Application Number
- CN202511133016.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-13
- Publication Date
- 2025-11-21
AI Technical Summary
Existing vanadium-titanium-based SCR denitration catalysts suffer from low activity and poor stability after long-term operation due to heavy metal adsorption, ammonium sulfate coverage, and support structure collapse, making it difficult to meet the requirements of long-term industrial operation.
Heavy metals and ammonium sulfate were removed by ultrasonic treatment with a mixed solution of ethylenediaminetetraacetic acid and hydrofluoric acid. The structure of TiO2 support was reconstructed by hydrothermal reaction. Ce and Zr were added to form CeO2-ZrO2 solid solution. WO3 and V2O5 were loaded with microwave assistance and gradient calcination was performed to form a V2O5-WO3-CeO2-ZrO2-TiO2 five-member interface.
It restores the activity and stability of the catalyst, improves denitrification efficiency, extends service life, has excellent resistance to sulfur poisoning, and is suitable for high-velocity industrial flue gas scenarios.
Smart Images

Figure BDA0005547283270000131 
Figure BDA0005547283270000141 
Figure BDA0005547283270000142
Abstract
Description
Technical Field
[0001] This invention relates to the field of denitrification catalyst regeneration technology, and in particular to a method for preparing a regenerated denitrification catalyst based on a reconstructed bulk support. Background Technology
[0002] In the field of industrial flue gas treatment, vanadium-titanium based selective catalytic reduction (SCR) denitrification catalysts are highly effective at removing nitrogen oxides (NOx). x Its performance makes it widely used in coal-fired power plants and other applications. However, after long-term operation, it is prone to deactivation due to multiple factors: heavy metals such as As and Pb in the flue gas are deactivated through chemical adsorption (e.g., As...). 3+ The active sites are blocked by the formation of As-O-Ti bonds with the oxygen in the TiO2 lattice or by physical deposition; SO3 reacts with unreacted NH3 to form ammonium sulfate salts such as (NH4)2SO4 and NH4HSO4, which cover the catalyst surface; high temperature causes the TiO2 support to sinter, resulting in a decrease in specific surface area and collapse of pore structure; active components such as V2O5 and WO3 are volatilized with the flue gas or washed away.
[0003] Existing regeneration technologies mostly employ simple acid washing to remove soluble deposits or add active components, but these methods struggle to address the strong binding of heavy metals to the support and cannot repair the deterioration of the support's bulk structure. This results in regenerated catalysts exhibiting low activity, poor stability, and denitrification efficiency that is only 60%-70% of that of fresh catalysts, along with short cycle life, failing to meet the demands of long-term industrial operation. Therefore, developing a regeneration method that can completely detoxify, reconstruct the support structure, and restore catalytic performance is crucial for the resource utilization of spent vanadium-titanium-based denitrification catalysts. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the prior art and to propose a method for preparing a regenerated denitrification catalyst based on a reconstructed bulk support.
[0005] To achieve the above objectives, the present invention provides a method for preparing a regenerated denitration catalyst based on a reconstructed bulk support, comprising the following steps:
[0006] S1. Waste vanadium-titanium-based denitrification catalyst with a particle size of 2-3 mm is added to a mixed solution of ethylenediaminetetraacetic acid (EDTA) and hydrofluoric acid. The solution is heated to 50-60℃, stirred, and ultrasonically treated for 2-4 hours. After filtration, washing, and drying, the detoxified carrier is obtained. During the process, EDTA acts as a strong chelating agent, and its main form under acidic conditions is HY. 2- "Y" represents the anionic skeleton of EDTA (i.e., ethylenediaminetetraacetic acid ion, chemical formula C). 10 H 12 N2O8 2- "H2Y" 2-This indicates that EDTA molecules dissociate into two H atoms in an acidic environment with a pH of 3.0-3.5. + The resulting ionic form carries two negative charges. The amino and carboxyl groups in its molecule can form stable water-soluble chelates with heavy metal ions. These chelates detach from the catalyst surface after coordinating with each other. Hydrofluoric acid (HF) can dissolve silicon-based fly ash deposits under acidic conditions. Simultaneously, the acidic environment promotes the dissolution of ammonium sulfate. The cavitation effect generated by ultrasonic vibration can disrupt the diffusion boundary layer on the catalyst surface, accelerating the diffusion of chelates and dissolved ammonium sulfate into the solution, thus improving removal efficiency. The chemical reaction equations occurring during this process are as follows:
[0007] Chelation reaction of EDTA with heavy metals: M n+ +HY 2- →MY (n-2)- +2H + M n+ Indicates heavy metal ions;
[0008] S2. In a hydrothermal reactor, add the detoxified carrier and titanium sol and stir for 10-20 min. Then add cerium nitrate hexahydrate and zirconium nitrate pentahydrate, raise the temperature to 180-200℃, and hydrothermally react for 8-12 h. Cool to room temperature, centrifuge to separate the product, wash with deionized water, and transfer the product to a muffle furnace. Under a nitrogen atmosphere, raise the temperature to 300-500℃ at a rate of 5℃ / min and calcine for 2-4 h to obtain the reconstructed bulk carrier. During the process, the titanium sol hydrolyzes under hydrothermal conditions to generate TiO2 nanocrystals, which bond with the TiO2 lattice on the surface of the detoxified carrier through hydroxyl groups, inducing the carrier to reconstruct from the sintered state into a nanorod array structure dominated by the anatase phase, restoring the specific surface area. Cerium nitrate hexahydrate and zirconium nitrate pentahydrate decompose into Ce during the hydrothermal process. 3+ Zr 4 + Because the ionic radius is similar to that of Ti 4+ Approaching, capable of replacing Ti in the TiO2 lattice 4+ Introducing oxygen vacancy defects enhances the electronic conductivity and the number of acidic sites on the support. Calcination at 300-500℃ in a nitrogen atmosphere fixes the reconstructed crystal structure, preventing oxygen vacancy collapse and forming a stable reconstructed bulk phase (anatase TiO2-CeO2-ZrO2 solid solution). The chemical reaction equations occurring during this process are as follows:
[0009] Hydrolysis and condensation of tetrabutyl titanate:
[0010] Ti(OC4H9)4 + 4H2O → TiO2·2H2O↓ + 4C4H9OH (hydrolysis) 2TiO2·2H2O → 2TiO2 + 4H2O (condensation, under hydrothermal conditions);
[0011] Ce and Zr salt decomposition (hydrothermal and roasting processes):
[0012] Nitrate ions undergo hydrolysis under high temperature and pressure.
[0013] Ce(NO3)3·6H2O→Ce 3+ +3NO3 - +6H2O, Ce 3+ +3OH - →Ce(OH)3↓
[0014] Zr(NO3)4·5H2O→Zr 4+ +4NO3 - +5H2O, Zr 4+ +4OH - →Zr(OH)4↓
[0015] 2Ce(OH)3→Ce2O3+3H2O (partial Ce) 3+ In step S4, upon contact with oxygen, it is further oxidized to CeO2: 4Ce2O3 + O2 → 8CeO2
[0016] Zr(OH)4→ZrO2+2H2O;
[0017] S3. The reconstructed phase support was added to an ammonium paratungstate solution, heated to 60°C, and treated with microwave irradiation at 300W for 20-40 minutes. The product was separated by centrifugation, washed with deionized water, dried, and then added to an ammonium metavanadate-oxalic acid mixed solution. The temperature was raised to 50°C, and microwave irradiation was applied at 200W for 20-30 minutes. The product was separated by centrifugation, washed with deionized water, and dried to obtain the precursor. During the process, WO4 in the ammonium paratungstate solution... 2- At 60℃ and under microwave radiation, the Lewis acid sites (Ti) on the surface of the reconstructed carrier are reconstructed through electrostatic attraction. 4+ Empty orbitals coordinate to form stable Ti-OW bonds, achieving uniform dispersion of the WO3 precursor. In ammonium metavanadate-oxalic acid mixed solutions, oxalic acid can react with VO3. - Formation of a soluble complex ([VO(C2O4)2]) 3- Under 50℃ and microwave radiation, the precursor binds to the Bronsted acid sites (-OH) on the support surface via hydrogen bonding, achieving directional anchoring of the V2O5 precursor. The chemical reaction equations that occur during this process are as follows:
[0018] Tungsten species and carrier coordination:
[0019] Ti 4+ +WO4 2- →Ti-O-WO3 -
[0020] Combination of vanadium species with oxalic acid:
[0021] VO3 - +2H₂C₂O₄→[VO(C₂O₄)₂] 3- +2H₂O+H + ;
[0022] S4. Place the precursor in a tube furnace and heat it to 250-300℃ at a heating rate of 2℃ / min under a nitrogen atmosphere, hold it at that temperature for 1-2 hours, then switch to an air atmosphere and heat it to 450-500℃ at a heating rate of 1℃ / min, hold it at that temperature for 3-5 hours, cool it to room temperature, and sieve it to 10-20 mesh to obtain the regenerated denitrification catalyst based on the reconstructed bulk phase support.
[0023] Preferably, the waste vanadium-titanium-based denitrification catalyst in S1 refers to a catalyst with TiO2 as a support, containing 0.5-2 wt% of active component vanadium pentoxide, 3-5 wt% of auxiliary agent tungsten trioxide, and poisoning elements As, Pb, Hg, Cd, and Zn, with a total content of 0.1-0.3 wt%, and 5-10 wt% of ammonium sulfate deposits.
[0024] Preferably, the waste vanadium-titanium-based denitrification catalyst and the mixed solution in S1 are in a weight ratio of 1:6-10.
[0025] Preferably, in the S1 mixture of ethylenediaminetetraacetic acid and hydrofluoric acid, the concentration of ethylenediaminetetraacetic acid is 0.05-0.1 mol / L, the concentration of hydrofluoric acid is 0.5-1 wt%, and the balance is deionized water, with the pH adjusted to 3.0-3.5 using nitric acid.
[0026] Preferably, in S2, the detoxification carrier, titanium sol, cerium nitrate hexahydrate and zirconium nitrate pentahydrate are in a weight ratio of 1:0.4-0.6:0.0075-0.015:0.0025-0.005.
[0027] Preferably, the titanium sol in S2 refers to the mixture of tetrabutyl titanate and anhydrous ethanol at a weight ratio of 1:3, with the pH adjusted to 2.0-2.5 by nitric acid and stirred for 30 minutes.
[0028] Preferably, in step S3, the reconstructed bulk carrier, paratungsten ammonium acid solution, and ammonium metavanadate-oxalic acid mixed solution are in a weight ratio of 1:3-7:3-7.
[0029] Preferably, the concentration of paratungstenic acid solution in S3 is 0.1-0.2 mol / L, the concentration of ammonium metavanadate in the ammonium metavanadate-oxalic acid mixed solution is 0.05-0.1 mol / L, and the concentration of oxalic acid is 0.1 mol / L.
[0030] Furthermore, the present invention also provides a regenerated denitrification catalyst based on a reconstructed bulk support, which is prepared by the above-described preparation method of the regenerated denitrification catalyst based on a reconstructed bulk support.
[0031] Preferably, the denitration catalytic mechanism of the regenerated denitration catalyst based on the reconstructed bulk support is as follows:
[0032] Under the action of a catalyst, the reducing agent NH3 reacts with NO in the flue gas. x (Mainly NO and NO2) undergo selective reactions to produce harmless N2 and H2O, i.e., the SCR reaction. A typical reaction formula is:
[0033] 4NH3 + 4NO + O2 → 4N2 + 6H2O (when NO is the main component)
[0034] 8NH3 + 6NO2 → 7N2 + 12H2O (when NO2 is the main component)
[0035] The Bronsted and Lewis acidic sites recovered during the catalyst reconstruction process can adsorb and activate NH3 through hydrogen bonding or coordination, providing sufficient activated NH4 for the reaction. + ;
[0036] Ce 3+ / Ce 4+ and Zr 4+ The doping introduces a large number of oxygen vacancies into the TiO2 lattice (due to lattice distortion caused by differences in ionic radii), which can adsorb and activate O2 in flue gas, while promoting NO... x The adsorption and activation of NO provide reactive oxygen species and activated NO for the reaction. x The reconstructed anatase TiO2 nanorod array has a high specific surface area and a porous structure, which can reduce the diffusion resistance of reactants and improve the diffusion efficiency of NH3 and NO. x The contact efficiency with the active site; through the loading of the active component in step S3 and the calcination activation in step S4, the active component forms a dispersed structure that is strongly bound to the support, specifically with the following effect:
[0037] The Redox Cycle of V₂O₅: As the main active component, V₂O₅ circulates through V₂O₅... 5+ / V 4+ The valence state of the electron cyclic transfers electrons, oxidizing the adsorbed NO to the more reactive NO2 (NO + V). 5+ +O - →NO2+V 4+ At the same time, it is re-oxidized to V by O2. 5+ (V 4+ +O2→V 5+ +O - This accelerates the SCR reaction process;
[0038] The role of WO3 as an additive: WO3 forms Ti-OW bonds with the support, which can stabilize the acidic sites of the support, enhance the dispersibility of V2O5, and reduce V through electronic effects. 5+ The reduction energy barrier is reduced, thus enhancing its redox activity;
[0039] The calcination activation in step S4 forms a stable five-membered interface, which enhances catalytic performance through charge transfer and defect synergy.
[0040] Ce 3+ / Ce 4+ and Zr 4+ Doping enhances the electronic conductivity of the support and promotes charge transfer between the active component and the support (e.g., V). 4+ To Ce 4+ Electron transport: V 4+ +Ce 4+ →V 5+ +Ce 3+ This accelerates the Redox cycle; the doping of CeO2-ZrO2 can preferentially adsorb SO2 in flue gas, reducing the poisoning of V2O5 active sites by SO2; at the same time, strong interfacial interactions (such as Ti-O-Ce and WO-Zr bonds) inhibit the high-temperature sintering of active components and prolong the catalyst life.
[0041] The catalyst significantly suppresses side reactions through structural design. V2O5 is the main active site for SO2 oxidation, but the introduction of WO3 can reduce the surface density of V2O5. At the same time, the oxygen vacancies of CeO2-ZrO2 preferentially adsorb O2, reducing the reaction with SO2.
[0042] The abundant acidic sites on the reconstructed support can fully adsorb NH3, preventing unreacted NH3 from escaping directly; at the same time, the highly efficient catalytic effect of the active component ensures that NH3 fully participates in the SCR reaction.
[0043] The beneficial effects of this invention are:
[0044] 1. This invention achieves targeted detoxification of spent catalysts through a synergistic ultrasonic treatment with a mixed solution of ethylenediaminetetraacetic acid and hydrofluoric acid. This method can efficiently remove heavy metals and ammonium sulfate deposits. The strong chelating properties of ethylenediaminetetraacetic acid can form stable water-soluble chelates with heavy metals such as As and Pb. Hydrofluoric acid can dissolve silicon-based fly ash. The ultrasonic cavitation effect accelerates the diffusion of pollutants, avoiding the problem of incomplete removal of heavy metal residues or deposits in traditional detoxification methods. This provides a clean substrate for subsequent carrier reconstruction and reduces the inhibition of catalytic activity by poisons.
[0045] 2. The bulk phase reconstruction process used in this invention can significantly optimize the structure and performance of the support. The TiO2 nanocrystals generated by in-situ hydrolysis of titanium sol bond with the lattice of the detoxified support, inducing the formation of anatase phase nanorod arrays and restoring the specific surface area and pore structure of the support. Ce and Zr doping introduces oxygen vacancies and forms a solid solution, enhancing the electronic conductivity and the number of acidic sites. This solves the problems of support sintering and insufficient active sites in traditional regeneration, providing a high-quality substrate for loading active components and improving the catalyst's adsorption and activation capabilities for reactants.
[0046] 3. The microwave-assisted gradient loading method used in this invention ensures uniform dispersion and strong binding of the active components. (WO4 in ammonium paratungstate) 2- Anchored to Lewis acid sites through coordination, the ammonium metavanadate-oxalic acid complex binds to Bronsted acid sites via hydrogen bonds. The internal heating effect of microwaves eliminates the concentration gradient, promotes the diffusion of active ions into the deeper layers of the support, avoids the defects of active component aggregation or weak binding force in traditional impregnation methods, strengthens the interfacial interaction between active components and the support, and improves the efficiency of catalytic reaction.
[0047] 3. The gradient roasting process employed in this invention enhances the catalyst's stability and resistance to poisoning. Low-temperature nitrogen pretreatment inhibits the volatilization of active components, while high-temperature air roasting promotes the conversion of precursors into WO3 and V2O5 active phases, forming a pentagonal synergistic interface of V2O5-WO3-CeO2-ZrO2-TiO2. This interface accelerates the redox cycle through charge transfer, Ce and Zr preferentially adsorb SO2 to reduce active site poisoning, and WO3 stabilizes acidic sites and inhibits SO2 oxidation, significantly improving the catalyst's resistance to sulfur poisoning and high-temperature stability, thus extending its service life.
[0048] 4. The catalyst prepared in this invention exhibits excellent flow performance. The nanorod array structure formed by the reconstructed bulk support creates interconnected channels. Combined with thorough detoxification treatment, pore blockage is avoided, reducing flue gas flow resistance, increasing porosity, and lowering pressure drop. This structural characteristic is suitable for high-velocity industrial flue gas scenarios, reducing system energy consumption while ensuring sufficient contact between reactants and active sites. It improves denitrification efficiency while considering the economics and practicality of industrial applications. Detailed Implementation
[0049] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0050] Example 1: A specific preparation method of a regenerated denitration catalyst based on a reconstructed bulk support, comprising the following steps:
[0051] S1. 100g of waste vanadium-titanium-based denitrification catalyst with a particle size of 2-3mm was added to 600g of a mixed solution of ethylenediaminetetraacetic acid and hydrofluoric acid (the concentration of ethylenediaminetetraacetic acid was 0.05mol / L, the concentration of hydrofluoric acid was 0.5wt%, and the balance was deionized water, with the pH adjusted to 3.0-3.5 by nitric acid). The solution was heated to 50℃, stirred, and ultrasonically treated for 2h. After filtration, washing, and drying, the detoxified carrier was obtained.
[0052] S2. In a hydrothermal reactor, add 90g of detoxified carrier and 36g of titanium sol (prepared by mixing tetrabutyl titanate and anhydrous ethanol in a weight ratio of 1:3, adjusting the pH to 2.0-2.5 with nitric acid, and stirring for 30min) and stir for 10min. Then add 0.675g of cerium nitrate hexahydrate and 0.225g of zirconium nitrate pentahydrate, raise the temperature to 180℃, and hydrothermally react for 8h. Cool to room temperature, centrifuge to separate the product, wash with deionized water, transfer the product to a muffle furnace, and calcine at a heating rate of 5℃ / min to 300℃ for 2h under a nitrogen atmosphere to obtain the reconstructed bulk carrier.
[0053] S3. Add 100g of the reconstructed bulk carrier to 300g of ammonium paratungstate solution with a concentration of 0.1mol / L, heat to 60℃, use microwave irradiation at a power of 300w for 20min, centrifuge to separate the product, wash with deionized water, dry, and then add to 300g of ammonium metavanadate-oxalic acid mixed solution (ammonium metavanadate concentration of 0.05mol / L, oxalic acid concentration of 0.1mol / L), heat to 50℃, use microwave irradiation at a power of 200w for 20min, centrifuge to separate the product, wash with deionized water, dry, and obtain the precursor;
[0054] S4. Place 100g of precursor in a tube furnace and heat it to 250℃ at a heating rate of 2℃ / min under a nitrogen atmosphere, hold it at that temperature for 1h, then switch to an air atmosphere and heat it to 450℃ at a heating rate of 1℃ / min, hold it at that temperature for 3h, cool it to room temperature, and sieve it to 10-20 mesh to obtain the regenerated denitrification catalyst based on the reconstructed bulk phase support.
[0055] Example 2: A specific preparation method of a regenerated denitration catalyst based on a reconstructed bulk support, comprising the following steps:
[0056] S1. 100g of waste vanadium-titanium-based denitrification catalyst with a particle size of 2-3mm was added to 800g of a mixed solution of ethylenediaminetetraacetic acid and hydrofluoric acid (the concentration of ethylenediaminetetraacetic acid was 0.075mol / L, the concentration of hydrofluoric acid was 0.75wt%, and the balance was deionized water, with the pH adjusted to 3.0-3.5 by nitric acid). The solution was heated to 55℃, stirred, and ultrasonically treated for 3h. After filtration, washing, and drying, the detoxified carrier was obtained.
[0057] S2. In a hydrothermal reactor, add 90g of detoxified carrier and 45g of titanium sol (prepared by mixing tetrabutyl titanate and anhydrous ethanol at a weight ratio of 1:3, adjusting the pH to 2.0-2.5 with nitric acid, and stirring for 30min) and stir for 15min. Then add 0.9g of cerium nitrate hexahydrate and 0.3g of zirconium nitrate pentahydrate, raise the temperature to 190℃, and hydrothermally react for 10h. Cool to room temperature, centrifuge to separate the product, wash with deionized water, transfer the product to a muffle furnace, and calcine at a heating rate of 5℃ / min under a nitrogen atmosphere to 400℃ for 3h to obtain the reconstructed bulk carrier.
[0058] S3. Add 100g of the reconstructed bulk carrier to 500g of ammonium paratungstate solution with a concentration of 0.15mol / L, heat to 60℃, use microwave irradiation at a power of 300w for 30min, centrifuge to separate the product, wash with deionized water, dry, and then add to 500g of ammonium metavanadate-oxalic acid mixed solution (ammonium metavanadate concentration of 0.075mol / L, oxalic acid concentration of 0.1mol / L), heat to 50℃, use microwave irradiation at a power of 200w for 25min, centrifuge to separate the product, wash with deionized water, dry, and obtain the precursor;
[0059] S4. The precursor is placed in a tube furnace and heated to 275°C at a heating rate of 2°C / min under a nitrogen atmosphere, and held for 1.5 h. Then, the atmosphere is switched to air and heated to 475°C at a heating rate of 1°C / min, and held for 4 h. After cooling to room temperature, it is sieved to 10-20 mesh to obtain the regenerated denitrification catalyst based on the reconstructed bulk phase support.
[0060] Example 3: A specific preparation method of a regenerated denitration catalyst based on a reconstructed bulk support, comprising the following steps:
[0061] S1. Add 100g of waste vanadium-titanium-based denitrification catalyst with a particle size of 2-3mm to 1kg of a mixed solution of ethylenediaminetetraacetic acid and hydrofluoric acid (the concentration of ethylenediaminetetraacetic acid is 0.1mol / L, the concentration of hydrofluoric acid is 1wt%, and the balance is deionized water, with the pH adjusted to 3.0-3.5 by nitric acid), heat to 60℃, and sonicate for 4h with stirring. After filtration, washing, and drying, the detoxification carrier is obtained.
[0062] S2. In a hydrothermal reactor, add 90g of detoxified carrier and 54g of titanium sol (prepared by mixing tetrabutyl titanate and anhydrous ethanol at a weight ratio of 1:3, adjusting the pH to 2.0-2.5 with nitric acid, and stirring for 30min) and stir for 20min. Then add 1.35g of cerium nitrate hexahydrate and 0.45g of zirconium nitrate pentahydrate, heat to 200℃, and hydrothermally react for 12h. Cool to room temperature, centrifuge to separate the product, wash with deionized water, transfer the product to a muffle furnace, and calcine at a heating rate of 5℃ / min to 500℃ for 4h under a nitrogen atmosphere to obtain the reconstructed bulk carrier.
[0063] S3. Add 100g of the reconstructed bulk carrier to 700g of ammonium paratungstate solution with a concentration of 0.2mol / L, heat to 60℃, use microwave irradiation at a power of 300W for 40min, centrifuge to separate the product, wash with deionized water, dry, and then add to 700g of ammonium metavanadate-oxalic acid mixed solution (ammonium metavanadate concentration of 0.1mol / L, oxalic acid concentration of 0.1mol / L), heat to 50℃, use microwave irradiation at a power of 200W for 30min, centrifuge to separate the product, wash with deionized water, dry, and obtain the precursor;
[0064] S4. The precursor is placed in a tube furnace and heated to 300°C at a heating rate of 2°C / min under a nitrogen atmosphere, and held for 2 hours. Then, the atmosphere is switched to air and heated to 500°C at a heating rate of 1°C / min, and held for 5 hours. After cooling to room temperature, the catalyst is sieved to 10-20 mesh to obtain the regenerated denitrification catalyst based on the reconstructed bulk phase support.
[0065] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that the mixed solution of ethylenediaminetetraacetic acid and hydrofluoric acid was replaced with a 5 wt% oxalic acid solution, while the other steps and parameters were completely consistent with Example 2.
[0066] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that in step S2, cerium nitrate hexahydrate and zirconium nitrate pentahydrate are not added, while the other steps and parameters are completely consistent with Example 2.
[0067] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that in step S2, the detoxification carrier was directly calcined in a muffle furnace at 300°C for 2 hours under a nitrogen atmosphere (without adding titanium sol, cerium nitrate hexahydrate and zirconium nitrate pentahydrate, and without hydrothermal reaction). The other steps and parameters were completely consistent with Example 2.
[0068] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that a traditional regeneration method is used. The specific preparation steps are as follows: A specific preparation method for a regenerated denitration catalyst based on a reconstructed bulk support includes the following steps:
[0069] S1. Add 100g of waste vanadium-titanium-based denitrification catalyst with a particle size of 2-3mm to 800g of sulfuric acid solution with a concentration of 5wt%, heat to 55℃, stir for 3h, collect the product by centrifugation, wash with deionized water to pH=6.5-7.0, and dry to obtain the detoxification carrier;
[0070] S2. Dissolve 0.075 mol of ammonium paratungstate and 0.0375 mol / L of ammonium metavanadate in 500 mL of deionized water, add 100 g of detoxification carrier to the above solution, stir in a water bath at 55 °C for 2 h, evaporate at 80 °C to a paste, and dry at 110 °C for 12 h to obtain the dried product.
[0071] S3. Place the dried product in a muffle furnace and heat it directly to 475°C at 2°C / min in air atmosphere, hold it at that temperature for 4 hours, cool it to room temperature, and sieve it to 10-20 mesh to obtain the regenerated denitrification catalyst based on the reconstructed bulk support.
[0072] Performance testing:
[0073] 1. Denitrification efficiency and temperature adaptability test: 5g of each of the catalysts prepared in Examples 1-3 and Comparative Examples 1-4 were loaded into fixed-bed reactors to simulate the flue gas conditions (NOx) of a coal-fired power plant. x With 500 ppm NO₂, 5% O₂, and N₂ as the balance gas, and 500 ppm NH₃ added as the reducing gas (gas flow rate of the mixed gas is 200 mL / min), the denitrification efficiency was tested at 50°C intervals within the temperature range of 150-450°C. During the test, data was recorded after each temperature point stabilized for 30 minutes, and the denitrification rate at different temperatures was calculated. Denitrification rate = (Inlet NO₂ - Inlet NO₂) / (Inlet NO₂ - Inlet NO₂) = 5% O₂ + 5% N₂ as the balance gas, and 500 ppm NH₃ added as the reducing gas. x Concentration - Export NO x Concentration) / Inlet NO x The concentration was multiplied by 100%, and the experimental results are shown in Table 1.
[0074] 2. Stability test against sulfur poisoning: The catalysts of Examples 1-3 and Comparative Examples 1-4 were used to introduce simulated flue gas containing SO2 = 1000 ppm (other components were the same as the simulated flue gas conditions of the coal-fired power plant) into a fixed-bed reactor. The reactor was continuously operated at 350℃ for 500 h. The denitrification efficiency was tested every 50 h, and the efficiency retention rate after 500 h was calculated. The denitrification retention rate = 500 h denitrification efficiency / 50 h denitrification efficiency × 100%. At the same time, the SO3 concentration at the reactor outlet was detected by ion chromatography, and the SO2 / SO3 oxidation rate was calculated. The oxidation rate = outlet SO3 concentration / inlet SO2 concentration × 100%. The experimental results are shown in Table 2.
[0075] 3. Catalyst Structure Testing: The specific surface area and pore distribution of the catalyst supports in Examples 1-3 and Comparative Examples 1-4 were tested using a Biometric Surface Area Analyzer (BET). The BET specific surface area (m²) was recorded.2 The experimental results (g / g) and average pore size (nm) are shown in Table 2.
[0076] 4. Long-term cycle life and pressure drop test: The catalysts of Examples 1-3 and Comparative Examples 1-5 were loaded into simulated flue gas pipelines (catalyst bed height 10cm, diameter 5cm), and actual power plant flue gas (pretreated by dust removal and desulfurization, NO = 400-600ppm, NH3 = 400-600ppm, O2 = 4-6%) was introduced. The system was continuously operated for 20,000 hours at 350℃ and a gas flow rate of 1.5m / s. The pressure difference (pressure drop) before and after the bed was tested, and the porosity was calculated. Porosity = (1 - bed pore blockage rate) × 100%. The experimental results are shown in Table 2.
[0077] Table 1. Results of Denitrification Efficiency and Temperature Adaptability Tests
[0078]
[0079]
[0080] Table 2. Results of sulfur poisoning resistance, catalyst structure, long-term cycle life, and pressure drop tests.
[0081]
[0082] Performance Analysis:
[0083] As can be seen from the experimental data in Tables 1 and 2, Examples 1-3, by employing a complete process of targeted detoxification, bulk phase reconstruction, microwave-assisted active component loading, and gradient calcination, outperformed the comparative examples in core indicators such as denitrification efficiency, sulfur poisoning resistance, carrier structural integrity, and flow performance. Overall, they exhibited higher catalytic activity, stronger environmental adaptability, and more durable stability, fully demonstrating the superiority of the "reconstructed bulk carrier + precise control" technical approach. Among the various examples, Example 2 had the most reasonable synergistic matching of process parameters, and its comprehensive performance in terms of wide-temperature-range denitrification efficiency, sulfur resistance, carrier structural stability, and pore flow performance was superior to other examples, making it the optimal solution in terms of overall performance.
[0084] From the perspective of denitrification efficiency and temperature adaptability, the superior performance of Example 2 stems from its unique microstructure and interfacial interactions. After bulk phase reconstruction, the support formed a TiO2 nanorod array dominated by the anatase phase. This structure significantly increased the specific surface area, providing ample active sites for the catalytic reaction. Simultaneously, Ce... 3+ / Zr 4+ The doping ion radius and Ti 4+ Unlike others, it successfully replaced part of the Ti in the TiO2 lattice. 4+This introduces a large number of oxygen vacancies, which can not only adsorb and activate O2 in the flue gas (forming reactive oxygen species O2), but also... - It can also promote NO x Adsorption and activation of (NO→NO) - This provides abundant active intermediates for the SCR reaction. Furthermore, the active components V₂O₅ and WO₃ are stably anchored to the support surface through chemical bonds (Ti-OV, Ti-OW), forming a five-membered synergistic interface of V₂O₅-WO₃-CeO₂-ZrO₂-TiO₂ that accelerates electron transfer and enhances the V₂O₅-WO₃-CeO₂-ZrO₂-TiO₂. 5+ With V 4+ The Redox loop (V 5+ →V 4+ →V 5+ This allows NH3 and NO to react within a wide temperature range of 150-450℃. x The reactions of the control group were all carried out efficiently, while the control group showed a decline in performance due to the lack of carrier reconstruction, resulting in a small specific surface area, insufficient active sites, or weak binding of active components.
[0085] From the perspective of sulfur poisoning resistance, the advantage of Example 2 stems from the special interface and chemical bonding effects formed by Ce / Zr doping. Ce and Zr form a stable CeO2-ZrO2 solid solution in the support, which is tightly bound to the TiO2 support through Ce-O-Ti and Zr-O-Ti bonds. This strong interaction not only enhances the structural stability of the support but also endows it with excellent sulfur resistance. 3+ It exhibits excellent redox properties, preferentially adsorbing SO2 in flue gas and converting it into stable Ce2(SO4)3, reducing the contact between SO2 and the active component V2O5, thereby inhibiting the formation of V2(SO4)3 (V2O5 readily reacts with SO3 to form the toxic species V2(SO4)3). Simultaneously, the presence of WO3 reduces the surface activity of V2O5 through electronic effects, decreasing the oxidation of SO2 to SO3 (SO2 + 1 / 2O2 → SO3), and further reducing the deposition of ammonium sulfate salts ((NH4)2SO4, NH4HSO4) at the active sites. Furthermore, the abundant oxygen vacancies in the reconstructed support can stabilize V2O5. 5+ The valence state of the sulfur species is maintained to prevent it from being reduced and deactivated by sulfur species. However, the control group, lacking such interfacial synergistic and inhibitory mechanisms, exhibits reduced resistance to sulfur poisoning.
[0086] From the perspective of carrier structural characteristics, the carrier in Example 2 formed a stable and optimized microstructure after bulk phase reconstruction. During the hydrothermal process, the TiO2·2H2O nanocrystals generated by the hydrolysis of tetrabutyl titanate bonded to the TiO2 on the surface of the detoxified carrier through hydroxyl bonds (Ti-OH+HO-Ti→Ti-O-Ti+H2O), inducing the carrier to reconstruct from the sintered state into a regular nanorod array, forming a through-hole structure. This structure not only makes the specific surface area and average pore size of the carrier larger, but also reduces the reactants (NH3, NO) x The diffusion resistance within the carrier improves the contact efficiency between the reactant species and the active site. Meanwhile, Ce... 3+ and Zr 4 + The uniform doping of TiO2 induces lattice distortion, suppressing the growth and sintering of TiO2 grains at high temperatures (traditional supports are prone to grain agglomeration and a decrease in specific surface area due to high temperatures), thus maintaining the long-term stability of the support structure. In contrast, the comparative example, lacking bulk reconstruction or doping, is prone to sintering, resulting in lower specific surface area and pore size, and poorer structural stability.
[0087] From the perspective of pressure drop and porosity, the superior flow performance of Example 2 stems from its regular nanorod array structure. During the reconstruction process, under the regulation of Ce / Zr ions, TiO2 nanorods grow oriented along specific crystal planes, forming uniform and unobstructed gaps between the nanorods, constituting efficient airflow channels. This structure reduces local resistance during flue gas flow, resulting in higher porosity and lower pressure drop. Furthermore, the targeted detoxification step thoroughly removes silicon-based fly ash and ammonium sulfate deposits from the spent catalyst, preventing pore blockage and further ensuring smooth airflow. In contrast, the comparative example suffers from decreased porosity and increased pressure drop due to residual contaminants clogging the carrier pores or structural collapse.
[0088] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing a regenerated denitration catalyst based on a reconstructed bulk support, characterized in that, Includes the following steps: S1. Add waste vanadium-titanium-based denitrification catalyst with a particle size of 2-3 mm to a mixed solution of ethylenediaminetetraacetic acid and hydrofluoric acid, heat to 50-60℃, stir, and sonicate for 2-4 hours. After filtration, washing, and drying, the detoxification carrier is obtained. S2. In a hydrothermal reactor, add the detoxified carrier and titanium sol and stir for 10-20 min. Then add cerium nitrate hexahydrate and zirconium nitrate pentahydrate, raise the temperature to 180-200℃, and hydrothermally react for 8-12 h. Cool to room temperature, centrifuge to separate the product, wash with deionized water, transfer the product to a muffle furnace, and calcine at 300-500℃ for 2-4 h under a nitrogen atmosphere at a heating rate of 5℃ / min to obtain the reconstructed bulk carrier. S3. Add the reconstructed bulk carrier to an ammonium paratungstate solution, heat to 60℃, apply microwave radiation at 300W for 20-40 min, centrifuge to separate the product, wash with deionized water, dry, add to an ammonium metavanadate-oxalic acid mixed solution, heat to 50℃, apply microwave radiation at 200W for 20-30 min, centrifuge to separate the product, wash with deionized water, dry to obtain the precursor; S4. Place the precursor in a tube furnace and heat it to 250-300℃ at a heating rate of 2℃ / min under a nitrogen atmosphere, hold it at that temperature for 1-2 hours, then switch to an air atmosphere and heat it to 450-500℃ at a heating rate of 1℃ / min, hold it at that temperature for 3-5 hours, cool it to room temperature, and sieve it to 10-20 mesh to obtain the regenerated denitrification catalyst based on the reconstructed bulk phase support.
2. The method for preparing the regenerated denitration catalyst based on a reconstructed bulk support according to claim 1, characterized in that, The waste vanadium-titanium-based denitrification catalyst in S1 refers to a catalyst with TiO2 as a support, containing 0.5-2 wt% of active component vanadium pentoxide, 3-5 wt% of auxiliary agent tungsten trioxide, and poisoning elements As, Pb, Hg, Cd, and Zn, with a total content of 0.1-0.3 wt%, and 5-10 wt% of ammonium sulfate deposits.
3. The method for preparing the regenerated denitration catalyst based on a reconstructed bulk support according to claim 1, characterized in that, The waste vanadium-titanium-based denitrification catalyst and the mixed solution in S1 are in a weight ratio of 1:6-10.
4. The method for preparing the regenerated denitration catalyst based on a reconstructed bulk support according to claim 1, characterized in that, In the S1 mixed solution of ethylenediaminetetraacetic acid and hydrofluoric acid, the concentration of ethylenediaminetetraacetic acid is 0.05-0.1 mol / L, the concentration of hydrofluoric acid is 0.5-1 wt%, and the balance is deionized water, with the pH adjusted to 3.0-3.5 using nitric acid.
5. The method for preparing the regenerated denitration catalyst based on a reconstructed bulk support according to claim 1, characterized in that, In S2, the detoxification carrier, titanium sol, cerium nitrate hexahydrate, and zirconium nitrate pentahydrate are in a weight ratio of 1:0.4-0.6:0.0075-0.015:0.0025-0.
005.
6. The method for preparing the regenerated denitration catalyst based on a reconstructed bulk support according to claim 1, characterized in that, The titanium sol in S2 refers to the mixture of tetrabutyl titanate and anhydrous ethanol at a weight ratio of 1:3, with the pH adjusted to 2.0-2.5 by nitric acid and stirred for 30 minutes.
7. The method for preparing the regenerated denitration catalyst based on a reconstructed bulk support according to claim 1, characterized in that, In S3, the reconstructed bulk carrier, paratungsten ammonium acid solution, and ammonium metavanadate-oxalic acid mixed solution are in a weight ratio of 1:3-7:3-7.
8. The method for preparing the regenerated denitration catalyst based on a reconstructed bulk support according to claim 1, characterized in that, The concentration of paratungsten ammonium acid solution in S3 is 0.1-0.2 mol / L, the concentration of ammonium metavanadate in the ammonium metavanadate-oxalic acid mixed solution is 0.05-0.1 mol / L, and the concentration of oxalic acid is 0.1 mol / L.
9. A regenerated denitrification catalyst based on a reconstructed bulk support, prepared by the method described in any one of claims 1-8.